The rise of ‘the Joshua generation?’: perspectives and attitudes on Facebook activism in Zimbabwe. - Shumba, Nyasha G. (Midlands State University, 2017)
The research focuses on Facebook users’ perceptions and attitudes of social media activism in Zimbabwe. Following a rise in social media campaigns in Zimbabwe, particularly in 2016, political participation has shifted to social media with a number of people demonstrating awareness and interest in the national issues. Drawing insights from Critical Discourse Analysis, this research discusses how the Facebook community responds to this new dispensation of social media activism. By focusing on the comments posted on Facebook handle “ThisFlag-IfulegiLeyi-Mureza” in response to a video posted as part of the fight against state failure in Zimbabwe, the research examines how Facebook users imagine new leaders in the mould of the Biblical Joshua and share insights on the several aspects which are deemed to matter as far as changes in the political field are concerned.